Physiological and Transcriptome Analysis of Exogenous L-Arginine in the Alleviation of High-Temperature Stress in Gracilariopsis lemaneiformis - Jun Zhang; Shixia Liu; Chaoyang Hu; Xiaojiao Chen; Xue Sun; Nianjun Xu (Frontiers in Marine Science, 2021)
Gracilariopsis lemaneiformis ( G. lemaneiformis ) is an important marine red macroalgae with high economic and ecological value all over the world. To date, global warming is a key issue that has a great impact on all living organisms, such as macroalgae. L-arginine (Arg) is a precursor of nitric oxide (NO) and polyamines (PAs), which can induce stress defense responses in land plants. However, its role in inducing algae resistance at high temperature (HT) is unclear. In this study, G. lemaneiformis thalli were treated with different concentrations of Arg to investigate its effect and the mechanism on the tolerance of G. lemaneiformis against HT stress. It turned out that exogenous Arg significantly alleviated the HT-induced oxidative damage as indicated by a markedly decrease in malondialdehyde (MDA) content. Notably, Arg remarkably improved the relative growth rate (RGR) and phycobiliprotein (PBP) contents of G. lemaneiformis at HT. Moreover, Arg significantly elevated the activities of antioxidant enzymes, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), to efficiently scavenge reactive oxygen species (ROS). In addition, it also promoted the accumulation of free amino acids (AAs) as compared to those in the control treatment (CK) group under HT conditions. To investigate the mechanism of G. lemaneiformis to Arg, a transcriptome analysis was performed and revealed 1,414 and 3,825 differentially expressed genes (DEGs) in Arg-treated groups as compared to CK groups at 24 and 48 h of HT stress, respectively. Results showed that Arg significantly upregulated the expression of genes encoding antioxidant enzymes, heat shock proteins, and triggered transcription factors (TFs) signaling during HT stress. Moreover, Arg enhanced the DEGs involved in arginine and proline (Pro) metabolism, AAs biosynthesis, glycolysis, tricarboxylic acid (TCA) cycle, and oxidative phosphorylation. These results may help in understanding the role of Arg in G. lemaneiformis resistance to HT and provide a practical viewpoint for obtaining heat-tolerant G. lemaneiformis to further promote the development of the cultivated seaweed industry in the future.